ANALISIS HUBUNGAN KARAKTERISTIK ANTARA VOLUME, KECEPATAN, DAN KEPADATAN ARUS LALU LINTAS DENGAN MENGGUNAKAN MODEL GREENSHIELDS (Studi Kasus: Jalan Diponegoro, Kota Surabaya) - Nova Aqshal Dwicahyo; Hendrata Wibisana (Racic : Rab Construction Research, 2025)
Diponegoro Street acts as the main artery connecting activity centers, including educational, economic, business activities and others. The presence of vehicle movements, especially during rush hours, especially towards Sidoarjo, has resulted in a decrease in performance on this road section and an increase in traffic volume. In this research, an analysis of the relationship between the three main components of traffic flow, namely volume, speed and density, was carried out using the Greenshields Method. The results of the analysis on Jalan Diponegoro show that the largest R2 value is on Monday in Segment 1 (Sidoarjo direction) with a value of 0.802. The variables in this segment have their respective values, namely Qmax of 2742.86 pcu/hour, Vf of 38,304 km/h, Vm of 19,152 km/hour, and Dm of 143,214 pcu/km. With an R2 value close to +1, it can be concluded that the conditions in Segment 1 on Jalan Diponegoro Surabaya as a whole tend to be close to results in accordance with actual field conditions